Ketorolac Administration with Ketorolac and Bilateral Superficial Cervical Plexus Block's Comparison to Total Post-Thyroidectomy Analgesic Rescue Needs - Fathir, Sandi; Suwarman, Suwarman; Erlangga, Muchammad Erias (Indonesian Journal of Multidisciplinary Science, 2023)
Thyroidectomy is generally performed by a surgeon with a short operating duration. Inadequate postoperative pain treatment results in several physiological and psychological outcomes, including prolonged hospital stays and the development of chronic pain. This study aims to compare the administration of ketorolac with a combination of ketorolac and bilateral superficial cervical plexus blocks to the total need for analgetic rescue after thyroidectomy surgery. This study used an experimental study with a single-blind randomized control trial method for both study groups. After surgery, group A was given an IV injection of 30 mg ketorolac, while group B was given IV injections of 30 mg ketorolac and bilateral superficial cervical plexus block under ultrasound guidance and 10 ml of 0.25% bupivacaine on each side of the neck before surgery was completed. Both groups would be monitored for 2 hours. The average value of total analgetic rescue needs in the patient group given ketorolac was 195.24 ± 72.72 mcg. While the total need for analgetic rescue in the group of patients who were given a combination of ketorolac and bilateral superficial cervical plexus blocks was 44.05 ± 19.21 mcg. The results of the unpaired T-test showed a p-value of 0.001. There is a significant difference in the total need for analgetic rescue in patients receiving ketorolac.